Curcumin for the clinical treatment of rheumatoid arthritis: a systematic review and meta-analysis of placebo-controlled randomized clinical trials - Fan, Yihua; Yi, Zhiqiang; Mao, Shijie; Wen, Jialu; Zhang, Jiwei; Zhang, Qiang; Liu, Ruihan (Frontiers in Immunology, 2026)
BackgroundThe efficacy and safety of curcumin in the treatment of rheumatoid arthritis (RA) remain controversial. We therefore conducted a meta-analysis to evaluate the efficacy and safety of curcumin in RA.MethodsWe searched PubMed, Embase, the Cochrane Library and Web of Science for relevant literature published up to July 30, 2025. The Cochrane risk of bias tool was used to assess bias in the included trials, and the Grade of Recommendations Assessment, Development and Evaluation (GRADE) framework was applied to evaluate the certainty of evidence. Meta-analyses were performed using Review Manager 5.3.ResultsSix studies involving 244 participants were included. The meta-analysis showed that curcumin significantly improved the following outcomes: American College of Rheumatology (ACR) 20 response (SMD = 4.35, 95%CI(2.22, 6.47), P < 0.0001; evidence certainty: very low), disease activity score(DAS-28) (SMD = -3.40, 95%CI(-5.29, -1.50), P = 0.0004; very low), erythrocyte sedimentation rate (ESR) level (SMD = -3.72, 95%CI(-5.26, -2.18), P < 0.00001; very low), C-reactive protein (CRP) level (SMD = -2.91, 95%CI(-4.42, -1.39), P = 0.0002; very low), visual analogue scale (VAS) score (SMD = -5.65, 95%CI(-6.95, -4.34), P < 0.00001; very low), tender joint count (TJC) (SMD = -2.84, 95%CI(-4.47, -1.22), P = 0.0006; very low), swollen joint count (SJC) (SMD = -4.11, 95%CI(-6.19, -2.03), P = 0.0001; very low), and rheumatoid factor (RF) level (SMD = -3.82, 95%CI(-4.62, -3.02), P < 0.00001; low).ConclusionCurrent evidence suggests that curcumin has a significant therapeutic effect on RA. However, given the limitations of this meta-analysis, future multicenter, large-sample, placebo-controlled randomized trials are warranted to further verify its efficacy and safety.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251147977, identifier CRD420251147977.